2007
DOI: 10.1177/0192513x06292703
|View full text |Cite
|
Sign up to set email alerts
|

Do Workplace Flexibility Policies Influence Time Spent in Domestic Labor?

Abstract: Using data from a U.S. midwestern sample of mothers and fathers, the authors examine whether using workplace flexibility policies alters time spent in housework and child care. They hypothesize that an individual's policy use will lead to more time in domestic labor and that his or her spouse's policy use will lead to less time in domestic labor. Several results support their hypotheses. Mothers who work part-time spend more time in housework and their husbands spend less time in housework. Also, mothers who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 32 publications
5
89
1
7
Order By: Relevance
“…Another study showed few significant relationships between respondents' use of various work-family policies and housework time (Noonan et al 2007). In this study, mothers who worked part-time spent more time in housework and their husbands spent less time in housework, but mothers with schedule flexibility spent less time in housework.…”
Section: Related Studiescontrasting
confidence: 58%
“…Another study showed few significant relationships between respondents' use of various work-family policies and housework time (Noonan et al 2007). In this study, mothers who worked part-time spent more time in housework and their husbands spent less time in housework, but mothers with schedule flexibility spent less time in housework.…”
Section: Related Studiescontrasting
confidence: 58%
“…This builds on the belief that the partner who makes use of family-friendly work arrangements is likely to invest the additional resources he/she gets (i.e., time or flexibility) in the home domain (Allen et al, 2013;Noonan, Estes, & Glass, 2007). The decision process theory of work and family (Poelmans, 2005) helps to explain why this may occur.…”
Section: Positive Crossover Processmentioning
confidence: 99%
“…Si les garderies subventionnées aident effectivement les femmes à retourner plus rapidement sur le marché de l'emploi, cette mesure, en plus d'être néfaste pour les enfants placés trop tôt, ne réduit absolument pas les obstacles sociaux minant l'accès du père au care (Fuwa et Cohen, 2007 ;Noonan 2013). De même, la régulation des heures de travail et les programmes visant à assurer une flexibilité d'emploi aux parents semblent bénéficier aux femmes jusqu'à un certain point, mais ne semblent rien changer à la situation des pères (Noonan et al, 2007). Ces quelques études sont, bien sûr, insuffisantes pour apporter une réponse définitive à la question de savoir si le quota du père est véritablement l'unique politique permettant de doter les individus d'une réelle égalité des chances.…”
Section: Vers Une Réelle éGalité Des Opportunitésunclassified